Q: 5 equals T on a F?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(f(g(t)))'=f'(g(t)) x g'(t) y=sqrt(3x-5) here f(t)=sqrt(t) and g(t)=3t-5, f'(t)=1/(2 sqrt(t)) and g'(t) = 3 So y'= f'(g(x)) x g'(x) = 1/(2 sqrt(3x-5) x 3 = 3/(2 sqrt(3x-5))

31

If -t = 5, then t = -5

t is 10. given t/5=2 multiply both sides by 5, then T = 10

(7 + 8)/3 = t Therefore, t = 5.

Related questions

5 Toes on a (Human) Foot

(f(g(t)))'=f'(g(t)) x g'(t) y=sqrt(3x-5) here f(t)=sqrt(t) and g(t)=3t-5, f'(t)=1/(2 sqrt(t)) and g'(t) = 3 So y'= f'(g(x)) x g'(x) = 1/(2 sqrt(3x-5) x 3 = 3/(2 sqrt(3x-5))

31

If -t = 5, then t = -5

I am assuming that k is the constant of proportionality so that f = k*a*t/b2 = 3*4*6/22 = 18

5 T on the F means 5 Toes on the Foot

f = 54

s=5 f+s=? Substitute 5 in for s.Substitute 1 in for f.f+s=f+5f=11+5 ={6}

50

-15°C = 5°F-15°C multiplied by 1.8 +32 = 5°F

-2

T-U-F-F- Puppy - 2010 Toast of T-U-F-F- Share-a-Lair 1-5 was released on: USA: 23 October 2010